“I’m hiding”: Using the Stories-Around-Poems to Explore the Role of Vulnerability in Today’s University Classrooms (LEARNing Landscapes, 2018)
This self-study examines the authors’ attempts to use narrative to create impactful and transformational learning experiences. The essay describes a process of auto-ethnographic inquiry during which the researchers explored critical incidents related to their use of stories in university classrooms. Further discussion of these experiences led to the creation of two individual poems that deepened our appreciation for the rich connections between narratives and confessional poetry. By using these research tools, the authors explore the role of vulnerability and self-disclosure in the creation of meaningful classroom encounters.
Keywords: self-study; narrative inquiry; storied-poems; narrative and identity